EDUKASI FISIOTERAPI TENTANG PENANGANAN RISIKO TERJADINYA NYERI PUNGGUNG BAWAH PADA KELOMPOK IBU HAMIL DI POSYANDU TERATAI KELURAHAN BAMBU KUNING WILAYAH KERJA PUSKESMAS REJOSARI - Mutiara, Sherly; Firdaus, Muhammad; Zaky, Abdul (LPPM Universitas Awal Bros, 2024)
Low back pain (LBP) is a common complaint among pregnant women, often caused by postural changes, weight gain, and hormonal fluctuations during pregnancy. This condition can significantly affect quality of life and daily functioning, yet community-based educational interventions remain limited. This community service program aimed to provide physiotherapy education to prevent and manage pregnancy-related LBP, particularly in local health post settings. The program was conducted at Posyandu Teratai, Bambu Kuning Subdistrict, under the Rejosari Health Center, in Pekanbaru City. The methods included educational sessions, practical stretching demonstrations, pre-test and post-test evaluations, and the distribution of digital materials for home-based practice. The results showed a significant increase in participants’ knowledge, with test scores improving from 60% to 85%. Participants showed strong enthusiasm during the practical sessions and reported that the techniques were helpful and easy to apply. Feedback included requests for broader content and more varied methods such as tutorial videos. As a follow-up, participants were encouraged to form peer support groups and continue practicing independently using the provided materials. In conclusion, this educational program effectively improved pregnant women’s knowledge and skills in managing LBP and made a positive contribution to maternal health through a structured, community-based approach.